Effect of annealing on bulk heterojunction organic solar cells based on copper phthalocyanine and perylene derivative - Kim, Inho; Jabbour, Ghassan E. (ELSEVIER SCIENCE SA, 2012)
We investigated the effects of annealing on device performances of bulk heterojunction organic solar cells based on copper phthalocyanine (CuPc) and N,N'-3,4,9,10-perylenetetracarboxylic diimide (PTCDI-C6). Blended films of CuPc and PTCDI-C6 with annealing at elevated temperature were characterized by measuring optical absorption, photoluminescence, and X-ray diffraction. Enhanced molecular ordering and increments in domain sizes of donor and acceptor for the blended films were observed, and their influences on device performances were discussed. Annealing led to substantial improvements in photocurrent owing to enhanced molecular ordering and formation of percolation pathways. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ACCEPTOR MOLECULAR HETEROJUNCTIONS; PHOTOVOLTAIC APPLICATIONS; FILMS